Pengaruh Pengeluaran Pemerintah Fungsi Ekonomi Dan Fungsi Pelayanan Umum Terhadap Kemiskinan di Provinsi Aceh - Yuliana Yuliana; Yulfrita Adamy; Danerlly Danerlly; Fajar Faqroni (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
Abstract: This study aims to determine and analyze the effect of Government expenditure on Economic Functions and Public Services on Poverty in Aceh Province in 2015-2019. This research is a quantitative research. The data used is secondary data in the form of financial report data from the official website of the Central Statistics Agency and the Directorate General of Fiscal Balance for the 2015-2019 period. Data analysis used panel data in Fixed effect regression model which was processed with Eviews-10. The results of the study show that: 1) Government Expenditure on Economic Functions has a positive and significant effect on poverty in Aceh Province in 2015-2019 with a probability value of 0.0394 <0.05. 2) Government Expenditures on Public Service Functions have a Negative and Significant Effect on Poverty in Aceh Province in 2015-2019 with a probability value of 0.0198 > 0.05. 3) adjusted R2 in this study is 0.998095, this means that the contribution of all independent variables in explaining the dependent variable is 99.80%. Keywords: Poverty, Government Expenditure on Economic Functions and Public Service, Fixed Effect Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh pengeluaran Pemerintah Fungsi Ekonomi dan Pelayanan Umum terhadap Kemiskinan di Provinsi Aceh Tahun 2015-2019. Penelitian ini merupakan penelitian Kuantitatif. Data yang digunakan adalah data sekunder berupa  data laporan keuangan dari website resmi Badan Pusat Statistik dan Direktorat Jendral Perimbangan Keuangan dengan periode tahun 2015-2019. Analisis data menggunakan data panel dalam model regresi Fixed effect yang diolah dengan Eviews-10. Hasil penelitian menunjukkan bahwa:1) Pengeluaran Pemerintah Fungsi Ekonomi berpengaruh positif dan signifikan terhadap kemiskinan di Provinsi Aceh Tahun 2015-2019 dengan nilai probability sebesar 0.0394 < 0,05. 2) Pengeluaran Pemerintah Fungsi Pelayanan Umumberpengaruh Negatif dan Signifikan terhadap Kemiskinan di Provinsi Aceh Tahun 2015-2019 dengan Nilai probability sebesar 0.0198 > 0.05. 3) adjusted R2 dalam penelitian ini sebesar 0.998095, hal ini berarti kontribusi seluruh variabel independen dalam menjelaskan variabel dependen yaitu sebesar 99.80%.Kata kunci : Kemiskinan, Pengeluaran Pemerintah Fungsi Ekonomi dan Pelayan Umu, Fixed Effect